Pengaruh Inflasi, Nilai Tukar Rupiah Dan Nilai Export Terhadap Pertumbuhan Ekonomi Indonesia Tahun 2014-2023 - Ahmad Yani, Yogi; Fauzi, Muhammad; Yani, Ahmad (ProBisnis : Jurnal Manajemen, 2025)
A country's rapid economic growth requires it to provide various facilities to support its people's welfare and advance itself. However, this is often hindered by suboptimal economic activity in the community due to the country's economic conditions during a certain period. This study aims to determine the effects of inflation, the rupiah exchange rate, and export value on economic growth in Indonesia. The study uses an associative approach to identify the relationship between the research variables. The results indicate that inflation, the rupiah exchange rate, and export value influence Indonesia's economic growth both partially and simultaneously..